Characterization of CELO Virus Proteins That Modulate the pRb/E2F Pathway - Lehrmann, Heike (American Society for Microbiology, 1999)
The avian adenovirus CELO can, like the human adenoviruses, transform several mammalian cell types, yet it lacks sequence homology with the transforming, early regions of human adenoviruses. In an attempt to identify how CELO virus activates the E2F-dependent gene expression important for S phase in the host cell, we have identified two CELO virus open reading frames that cooperate in activating an E2F-inducible reporter system. The encoded proteins, GAM-1 and Orf22, were both found to interact with the retinoblastoma protein (pRb), with Orf22 binding to the pocket domain of pRb, similar to other DNA tumor virus proteins, and GAM-1 interacting with pRb regions outside the pocket domain. The motif in Orf22 responsible for the pRb interaction is essential for Orf22-mediated E2F activation, yet it is remarkably unlike the E1A LxCxD and may represent a novel form of pRb-binding peptide.